Lehman Brothers: Sebuah Pembelajaran Restrukturisasi Bagi Indonesia - F.Yudhi Priyo Amboro (Fakultas Hukum, Universitas Internasional Batam, 2018)
The experience of Lehman Brothers’ restructuring, one of the big companies in the United States, is an attractive reference for all parties, especially related to the restructuring process with formal legal proceedings. The restructuring of large companies in Indonesia uses outside of formal legal proceedings approach, hence it is potentially diverted by the debtor and then violate the interests of its creditors. This paper opens the discourse of the importance of restructuring carried out using formal legal proceedings, and therefore a formal procedure for restructuring needs to be made in accordance with Indonesian conditions.